Risk scores for risk stratification in chronic coronary syndrome and their improvement by Gensini and SYNTAX scores. (14th October 2021) - Blaum, C; Bay, B; Kroeger, F; Gossling, A; Lorenz, T; Max, L; Zeller, T; Schnabel, R; Clemmensen, P; Westermann, D; Kirchhof, P; Blankenberg, S; et al.
Abstract: Introduction: There is a substantial residual risk in patients with chronic coronary syndrome (CCS). Risk scores could be useful tools to allocate intensified secondary preventive medications to address this residual risk. Whether their predictive value can be improved by addition of angiographic scores of the extent of coronary artery disease (CAD) is unknown. Purpose: To test and compare the predictive value of three externally developed risk scores for CAD and to investigate the effect of addition of SYNTAX and Gensini scores. Methods: We tested the TIMI risk score for secondary prevention (TRS 2°P), a risk score derived from the INVEST study, and the ABC-CHD model (see references 1–3) in 1280 patients with CCS from a contemporary observational CAD cohort ongoing since 2015 with a median follow-up of 3.6 years. In a second step we added SYNTAX and Gensini scores to the models. The endpoints tested were cardiovascular death and major adverse cardiovascular events (MACE), consisting of cardiovascular death, myocardial infarction and ischemic stroke. Results: All investigated scores yielded continuously increasing event rates for MACE and cardiovascular death with increasing score points obtained. As an example Figure 1 displays 3-year rates for cardiovascular death and MACE against the points obtained in the TRS 2°P, whilst also displaying the distribution of patients amongst the risk categories. The three scores showed modest predictive value for occurrence of cardiovascular death (c-indices 0.60, 0.64, 0.70 for TRS 2°P, INVEST score, ABC-CHD score, respectively). Addition of both SYNTAX and Gensini scores to the models yielded c-indices of 0.66, 0.69 and 0.70 respectively (Figure 2a). Similar predictive values were observed for the occurrence of MACE (c-indices 0.59, 0.60, 0.64 for TRS 2°P, INVEST score, ABC-CHD score, respectively) as well after addition of both SYNTAX and Gensini scores (c-indices 0.62, 0.63, 0.64, see Figure 2b). Conclusion: (I) Currently available risk scores are modestly predictive for the occurence of cardiovascular events in patients with CCS. (II) Addition of Gensini and SYNTAX scores improves their predictive value particularly in weaker risk scores. FUNDunding Acknowledgement: Type of funding sources: None.